Behaviour of Reinforced Concrete Slabs with Steel Fibers - Baarimah, A. O.; Sharifah Maszura, Syed Mohsin (IOP Publishing, 2017)
his paper investigates the potential effect of steel fiber added into reinforced concrete slabs. Four-point bending test is conducted on six slabs to investigate the structural behaviour of the slabs by considering two different parameters; (i) thickness of slab (ii) volume fraction of steel fiber. The experimental work consists of six slabs, in which three slabs are designed in accordance to Eurocode 2 to fulfil shear capacity characteristic, whereas, the other three slabs are designed with 17% less thickness, intended to fail in shear. Both series of slabs are added with steel fiber with a volume fraction of Vf = 0%, Vf = 1% and Vf = 2% in order to study the effect and potential of fiber to compensate the loss in shear capacity. The slab with Vf = 0% steel fiber and no reduction in thickness is taken as the control slab. The experimental result suggests promising improvement of the load carrying capacity (up to 32%) and ductility (up to 87%) as well as delayed in crack propagation for the slabs with Vf = 2%. In addition, it is observed that addition of fibers compensates the reduction in the slab thickness as well as changes the failure mode of the slab from brittle to a more ductile manner.